NF-κB inducing kinase (NIK) is an essential post-transcriptional regulator of T-cell activation affecting F-actin dynamics and TCR signaling. (November 2018) - Lacher, Sonja M.; Thurm, Christoph; Distler, Ute; Mohebiany, Alma N.; Israel, Nicole; Kitic, Maja; Ebering, Anna; Tang, Yilang; Klein, Matthias; Wabnitz, Guido H.; Wanke, Florian; Samstag, Yvonne; et al.
Abstract: NF-κB inducing kinase (NIK) is the key protein of the non-canonical NF-κB pathway and is important for the development of lymph nodes and other secondary immune organs. We elucidated the specific role of NIK in T cells using T-cell specific NIK-deficient (NIK ΔT ) mice. Despite showing normal development of lymphoid organs, NIK ΔT mice were resistant to induction of CNS autoimmunity. T cells from NIK ΔT mice were deficient in late priming, failed to up-regulate T-bet and to transmigrate into the CNS. Proteomic analysis of activated NIK −/- T cells showed de-regulated expression of proteins involved in the formation of the immunological synapse: in particular, proteins involved in cytoskeleton dynamics. In line with this we found that NIK-deficient T cells were hampered in phosphorylation of Zap70, LAT, AKT, ERK1/2 and PLCγ upon TCR engagement. Hence, our data disclose a hitherto unknown function of NIK in T-cell priming and differentiation. Highlights: NIK deficiency in T cells results in impaired generation of effector T-cells and subsequent resistance to EAE induction. NIK is important for Treg development but not for their maintenance. NIK is a posttranscriptional regulator in activated T cells. NIK affects expression of proteins involved in the immunological synapse formation and F-actin dynamics. NIK plays a crucial role in initial events of activated TCR signaling cascade.